Carbon isotope chemostratigraphy of the Yucca Formation from the Solitario, Big Bend Ranch State Park, Texas - Biebesheimer, E. J.; Suarez, M. B. (Frontiers in Earth Science, 2024)
The Yucca Formation is a Lower Cretaceous sedimentary unit present in West Texas. Based on its relative stratigraphic position in the Cretaceous succession of West Texas, it is expected that the Yucca Formation is of Albian and/or Aptian age. It is also expected that the carbon isotope excursions associated with OAE 1a and OAE 1b should be identified in the Yucca Formation. The goals of this project are to 1. construct a carbon isotope chemostratigraphic record of the Yucca Formation, and 2. correlate the Yucca Formation with strata of similar age using chemostratigraphy.163 samples were collected from Big Bend Ranch State Park (BBRSP) to determine the d 13 C value of bulk sedimentary organic matter. C-isotope values range from -27.02 ‰ to -18.42 ‰. Carbon isotope excursions (CIE) that are associated with the Aptian-Albian Boundary are identified as well as CIEs associated with Oceanic Anoxic Events (1a and 1b). This allows us to conclude that the Aptian-Albian boundary is recorded within the Yucca Formation strata at about 71 meters above the base of the section exposed in the Lower Shutup of the Solitario in Big Bend Ranch State Park. Regional correlation of the Yucca Formation to other chemostratigraphic records from other Cretaceous strata suggests that the Yucca Formation in BBRSP is time equivalent to the Sligo, Pine Island, James, Bexar, and a portion of the lower Glen Rose Formation on the Comanche Platform and to a portion of the lower Glen Rose Formation in Big Bend National Park.